Elderly left behind? How older workers can participate in the modern labor market - Oliver Falck; Valentin Lindlacher; Simon Wiederhold (EconPol Forum, 2022)
Digital skills are positively related to employment prospects and productivity of older workers. They also enable older workers to work in high-paying jobs. Fortunately, digital skills can be acquired and honed at all ages. Policymakers should incentivize employers to offer more training for the elderly and fund training programs in higher-education institutions. At present, the elderly show huge international differences in digital skills, larger than those for younger groups.
Keywords: 330